A Mobile Approach to Farmer-Computer Interaction - Maria João Ribeiro Marques (2017)
Agriculture has been responsible for sustaining and enhancing human life starting at least 105,000 years ago. Nowadays, traditional approaches to farming can be enhanced with technology, helping farmers make more informed decisions when it comes to their farming activities. Information and communication technologies, specifically mobile phones and tablets, are now enabling farmers to improve farm productivity and profitability, even in rural areas.However, due to limited technological proficiency a problem emerges. The adoption and acceptance of these solutions are dependent on the skill for handling and understanding digital media and this can be a challenge in specific demographics, where age can be a constraint and access to technology, in rural areas, be scarce.The aim of this study was to conduct a research at Fraunhofer AICOS centred around the potential end-users of a mobile application in the agricultural field. Therefore a User-centred Design methodology was followed, allowing to narrow the scope of the study, from Agriculture in general to Prevention and Control of the Grapevine Moth in Viticulture in the Douro Region of Portugal. In this process, explicit and implicit methods where used, such as Personas, Focus Groups, Individual Interviews, Field Observation and Usability Testing. Farmers and other stakeholders where involved in all phases of the design process, from requirements gathering, analysis, design and evaluation of the prototypes created.The outcome of this study was to accommodate and support farmers' needs and expectations while also creating guidelines and User Interface elements that'll inform future projects with similar end-users.